Clinical Implementation of Robust Multi-isocentric Volumetric Modulated Arc Radiotherapy for Craniospinal Irradiation. Issue 4 (April 2022) - Smyth, G.; Mowat, S.; Chia, K.; Robinson, K.; Warren-Oseni, K.; Welsh, L.C.; Blasiak-Wal, I.; Mandeville, H.C.
Abstract: Aims: To determine if multi-isocentric volumetric modulated arc radiotherapy for craniospinal irradiation (CSI-VMAT) can be implemented safely and accurately using robust optimisation in a commercially available treatment planning system. Our initial clinical experience is reported for the first 20 patients treated with the technique. Materials and methods: Patients received between 23.4 and 39.6 Gy (mode 23.4 Gy) in 13–22 fractions with CSI-VMAT. The heart mean dose was 4.2–10.3 Gy (median 5.3 Gy) for patients prescribed up to 24 Gy and 6.5–16.3 Gy (median 10.1 Gy) for patients receiving 35 Gy or more. The lung mean dose was 5.5–7.6 Gy (median 6.8 Gy) for patients prescribed up to 24 Gy and 6.9–11.1 Gy (median 10.0 Gy) for patients receiving 35 Gy or more. The robustness of the planning target volume D0.1cm3 and D99% to systematic errors in the isocentre superoinferior position of up to 5 mm was evaluated. These remained acceptable but were correlated to the length of the available beam overlap through the neck. Results: As of January 2021, one patient was deceased after 508 days and one patient was lost to follow-up after completing treatment. The median follow-up was 399 days (range 175–756 days) and progression-free survival was 131 days (34–490 days). Acute toxicities at Common Terminology Criteria for Adverse Events v5.0 grade 3+ included lowered white blood cell count (16/20), decreased platelet count (8/20), nausea (5/20), vomiting (2/20), pharyngeal mucositis (1/20) and oral mucositis (1/20). Three patients developed grade 4 neutropenia or decreased white blood cell count. Conclusions: CSI-VMAT can be implemented safely and accurately using robust optimisation functions in a commercially available treatment planning system. Highlights: Multi-isocentric craniospinal irradiation is implemented using a commercial system. Incidence of severe acute toxicities was low and follow-up to date is promising. Final plans are sufficiently robust to systematic superoinferior errors up to 5 mm. Delivery quality assurance can be streamlined with experience.